Seismic behaviour of low-ductile moment resistance frame under far field earthquake excitations considering soft-storey phenomenon - Abdul Rahman, Qotrunnada (2015)
Most of current Malaysian’s structures have not been designed for designs did not consider seismic excitation effect. Since Malaysia’s geography is far from earthquake prone region, the tremors, mostly non-lethal can be felt. The effects of seismic excitation on the stability and fragility of the building are now concerned by most researchers and engineers all over the world to mitigate structural damage and societal losses. This study focuses on the seismic performance of Reinforced Concrete (RC) Moment Resistance Frames (MRF) in Malaysia due to far field earthquake excitation, which has been designed to resist gravity and wind loads effects only. An ordinary building layout with different number of storeys (four, seven, and ten storeys) is selected in ways that represent the soft-storey phenomenon of RC building in Malaysia. Such structures have limited lateral load capacity to withstand against strong ground motion. Therefore, the outcomes of this study the vulnerability of typical RC, MRF structures in Malaysia motions and clarifies on the necessity of seismic retrofit for such structures